Competências e habilidades na formação em psicologia: os desafios do saber-fazer - Bernardes, Clarissa Tenório Ribeiro (2016)
After the Federal Constitution of 1988, the Brazilian educational policy undergoes profound changes. Under the aegis of sociointeractionists and socioconstrutivists theories, the curriculum changes from a disciplinary structure, which focuses on knowledge, now favoring an integrated structure, no longer supported in isolated content, but concerned with the development of skills and abilities that focus in concrete action on know-how. Thus, under the social constructivist theoretical construct whose greatest expression is César Coll, we try to analyse this work as the specific skills of psychology, expressed in the Guidelines that are developed in the practice of the psychology course . For this, our methodological approach initially favored an analysis of key documents that focus on this training - namely Diretrizes Curriculares, Projeto Pedagógico de Curso and the ENADE test - each representing one of the stages of the training cycle (planning, implementation, evaluation) and subsequently we conduct participant observation in Unsupervised Practice Classes I and II emphasizing health, where we analyzed, respectively, where these concepts emerge in the formal framework (legislation) and how they are developed with legal emphasis, where students are required to take the professional place. Finally, we identify some convergences and ruptures, especially magnified given the complexity of psychology, but that allowed us to raise some questions that can help in the training process.